Enrichement Books in Indonesia - Muhammad Thobroni; Ida Zulaeha; Hari Bakti Mardikantoro; Tommy Yuniawan (International Conference on Science, Education, and Technology, 2022)
Enrichment books are one type of book that supports teaching materials in schools. There have been many models of enrichment books compiled in Indonesia for various topics and learning needs. However, there is no research that systematically reviews the existence and development of enrichment books in Indonesia. A systematic review is needed to find a map of the distribution of enrichment books, especially on thematic, concept, and modeling aspects. This study examine the development of enrichment books in Indonesia in the treasury of scientific publications in Indonesia. The method used is Systematic Literature Review (SLR). Scientific publications are important indicators for the development of enrichment books that have received wide scientific appreciation. The more and more diverse scope of the study can be an indicator of developments in Indonesia. Because large scientific publications indicate that enrichment books in Indonesia are sufficient and very worthy to be researched, studied and published scientifically. The study was limited to finding categories based on Indonesian and non-Indonesian subjects; based on targets for primary, secondary and tertiary education; by types of fiction and nonfiction, as well as other categories. The results of this study provide an important contribution to scientific development in the field of SLR studies and research on the development of enrichment books in Indonesia. In addition, the study can also be used by the government to take book policies, as well as teachers and lecturers to develop enrichment books with similar topics but different models and different topics.